43 UHRF2 Is Expressed in Human Diffuse Large B Cell Lymphoma and Associated with Increased p53 Expression. (11th January 2018) - Freeman, Matthew; Sachs, Zohar; Forster, Colleen; Hallstrom, Timothy; Linden, Michael
Abstract: Objective: Diffuse large B cell lymphoma (DLBCL) is a neoplasm of large B lymphocytes with a diffuse growth pattern. Though morphologically homogeneous, there is heterogeneity in DLBCL biology. The World Health Organization (WHO) has divided DLBCL into different prognostic categories based on morphology, genetics, immunophenotype, and clinical presentation. Ubiquitin-like with PHD and ring finger domains 2 (UHRF2) protein is involved in cell-cycle regulation and is an important transcriptional co-activator of E2F1-induced cell death genes. Prior studies have suggested that UHRF2 may interact with p53. In previous studies, we demonstrated that UHRF2 varies in expression and localization in diverse human cancers, including one case of non-Hodgkin lymphoma. In the current study, our major objectives were to characterize the expression of UHRF2 in human DLBCL and correlate its expression patterns with pathologic and clinical features; the long-term outcome is to understand whether UHRF2 is an important regulator of DLBCL biology. Methods: After receiving an internal review board waiver, we performed a natural language search of the pathology database to identify nodal, primarily de novo, adult human DLBCL cases diagnosed at the University of Minnesota between 2003 and 2016. Hematoxylin and eosin (H&E) slides were reviewed by two authors (MF and ML) to verify the diagnosis and evaluate for specimen adequacy. After excluding needle core biopsies, 37 samples (36 patients) were included to construct a DLBCL tissue microarray (TMA). Clinical data were collected through electronic medical record searches. Control tissues from spleen, thymus, bowel, tonsil, and appendix, as well as the 37 samples were spotted randomly in triplicate to construct a 128-spot TMA. TMA slices were stained with H&E and CD3, Ki67, PAX-5, p53, and UHRF2 immunostains. All samples were evaluated by light microscopy and scored by two authors (MF and ML). Results: Cases represented 18 men and 18 women, with a mean age at diagnosis of 64 (range 21–84). All cases of DLBCL expressed UHRF2; however, there was variability in UHRF2 expression. We categorized cases into "high" and "low" UHRF2 expressing groups. Cases among the "high" group were more likely to be associated with a greater proportion of nuclei that overexpressed the p53 gene product (Fisher exact test, P < .05). However, UHRF2 expression did not correlate with a high Ki67 defined proliferative index, high percent tumor infiltrating T cells, nuclear PAX-5 expression, germinal center subtype, or overall survival. Conclusions: We conclude that UHRF2 is universally expressed in all DLBCL cases in our study, and there is an association between high expression of UHRF2 and overexpression of the p53 protein. This association may implicate a role of UHRF2 in lymphomagenesis and/or tumor maintenance in the subset of DLBCL cases that express high levels of p53.